2018
DOI: 10.31235/osf.io/g2sd6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

It’s Not Only What you Say, It’s Also How You Say It: The Strategic Use of Campaign Sentiment

Abstract: What explains the type of electoral campaign run by political parties? We provide a new perspective on campaigns that focuses on the strategic use of emotive language. We argue that the level of positive sentiment parties adopt in their campaigns depends on their incumbency status, their policy position, and objective economic conditions. We test these claims with a novel dataset that captures the emotive language used in over 400 party manifestos across eight European countries. As predicted, we find that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
17
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 38 publications
6
17
1
Order By: Relevance
“…The only other party whose MPs use a similarly low amount of positive emotions is the left-populist The Left. This finding is in line with previous research, which has found that populist politicians use positive emotions less often than the mainstream ones (Widmann 2019), and that the rhetoric of parties far from the ideological center also tends to be less positive (Crabtree et al 2018).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The only other party whose MPs use a similarly low amount of positive emotions is the left-populist The Left. This finding is in line with previous research, which has found that populist politicians use positive emotions less often than the mainstream ones (Widmann 2019), and that the rhetoric of parties far from the ideological center also tends to be less positive (Crabtree et al 2018).…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, our findings are in line with previous research in highlighting how politicians tend to use emotions strategically (Crabtree et al 2018). However, our paper adds an important insight to this conclusion.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“… Giger et al () show, for example, that party manifestos contain more references to general economic goals when economic conditions are poor and Crabtree et al () find that negative sentiments in party manifestos vary in a predictable fashion with the state of the economy.…”
mentioning
confidence: 99%